Association between physical activity levels and healing in people with venous leg ulcers: secondary analysis of prospective cohort data - Qiu, Yunjing; Osadnik, Christian R.; Brusco, Natasha K.; Sussman, Geoffrey; Reeves, Judy; Gleghorn, Leanne; Weller, Carolina D.; Team, Victoria (Frontiers in Medicine, 2023)
Aim To explore the relationship between physical activity levels and wound healing and recurrence in people with venous leg ulcers. Methods Questionnaires and medical records were used to collect data, with responses used to group participants into different physical activity groups. The differences in healing and recurrence outcomes of ulcers among different physical activity groups was compared using Chi-square, Kaplan Meier survival analysis, Cox proportional hazards regression analysis, and Kruskal-Wallis test. To measure the strength of association between physical activity levels and patient outcomes, Spearman's Rho tests were used. We used descriptive analysis to examine how physical activity levels change over 24 weeks. Results Participants were classified into four distinct groups based on physical activity levels reported at baseline and week 12. The survival analysis showed higher physical activity level was associated with shorter time to healing (log-rank test = 14.78, df=3; p = 0.002). The persistently moderate-to-vigorous group had a 7.3 fold increased likelihood of healing compared to the persistently sedentary group. High levels of physical activity were also associated with a better quality of life score at baseline (ρ = 0.41, p <0.000), week 12 (ρ = 0.36, p <0.001) and week 24 (ρ = 0.49, p <0.000). Most participants (48.5%) reported low levels of physical activity, which remained low for the entire study period. Conclusions An increased level of physical activity was linked to a shorter healing time and enhanced quality of life. Low levels of physical activity appeared common among people with venous leg ulcers.